2017
DOI: 10.1103/physrevb.96.054418
|View full text |Cite
|
Sign up to set email alerts
|

Toward pressure-induced multiferroicity in PrMn2O5

Abstract: The series of multiferroics RMn2O5 is extensively studied for its quasi-collinear spin arrangement, which results in an electrical polarization according to the exchange-striction model. Variations of the interatomic distances modified by the external pressure can strongly influence the multiferroic properties. Understanding this influence is of great importance, especially for the future realization of multiferroic devices. As PrMn2O5 is paraelectric at ambient pressure, it is the most suitable candidate to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The main result of our experiments is the observation of a pressure-induced PCM phase with propagation vector k = ( 1 2 0 1 2 ) in DyMn 2 O 5 and TbMn 2 O 5 despite their different propagation vectors at ambient pressure. Being also observed in YMn 2 O 5 and in PrMn 2 O 5 under high pressure [24], such periodicity most likely corresponds to a high-pressure ground state which is generic in the RMn 2 O 5 family. Assuming a planar structure, we find that the PCM phase must be associated with a lowering of symmetry along the c axis to the P 1 SG (see the Supplemental Material [32]).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The main result of our experiments is the observation of a pressure-induced PCM phase with propagation vector k = ( 1 2 0 1 2 ) in DyMn 2 O 5 and TbMn 2 O 5 despite their different propagation vectors at ambient pressure. Being also observed in YMn 2 O 5 and in PrMn 2 O 5 under high pressure [24], such periodicity most likely corresponds to a high-pressure ground state which is generic in the RMn 2 O 5 family. Assuming a planar structure, we find that the PCM phase must be associated with a lowering of symmetry along the c axis to the P 1 SG (see the Supplemental Material [32]).…”
Section: Discussionmentioning
confidence: 69%
“…In this paper, we address this question and pursue the idea that applying pressure is a good tool to unveil the mechanisms at the origin of these behaviors on a macroscopic scale [16,21] or microscopic one [22,23]. Previous neutron-diffraction studies on YMn 2 O 5 and PrMn 2 O 5 under high pressure have shown the onset of a pressure-induced commensurate phase (PCM), which appears at low pressure and progressively develops as pressure increases at the expense of both the ambient pressure CM and the ICM phases [22][23][24]. The PCM phase propagation vector k = ( 1 2 0 1 2 ) is the same as in BiMn 2 O 5 at ambient pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In these complex systems, the large effect of small variations in the interatomic distances and angles on the super-exchange integrals induces a strong dependence of the multiferroic properties on external factors. Indeed, an enhanced polarization has been observed under pressure (de la Cruz et al, 2006;Chaudhury et al, 2008) in the RMn 2 O 5 (R = Tb, Ho and Y) compounds and it has been associated with a new pressure-induced magnetic phase, recently shown by neutron measurements on Y (Deutsch et al, 2015;Kozlenko et al, 2015), Tb (Deutsch et al, 2018) and PrMn 2 O 5 (Peng et al, 2017). The dependence of the electric polarization of RMn 2 O 5 at ambient pressure as a function of the ionic radius of R 3+ .…”
Section: Introductionmentioning
confidence: 96%
“…Our previous study shows that although the ground states are diverse, the doping effects of some 3d ions on Ru sites show consistency. That is, Mn and Ti dopants induce or enhance the Mott insulating state and AFM coupling, while Cr, Fe, or Co enhances the FM coupling [19]. For example, in double layer ruthenates, Ca3Ru2O7, it shows an antiferromagnetic (AFM) transition at 56 K, which is then followed by a metal-insulator transition (MIT) at 48 K [20].…”
Section: Introductionmentioning
confidence: 99%
“…The spin direction switches from the a-axis (AFMa) for TMIT < T < TN to the b-axis (AFM-b) for T < TMIT [17,21]. As few as 3% Ti doping or 4% Mn doping on the ruthenium site can tune the system from a quasi-2D metallic state with AFM-b order to a Mott insulating state with a G-type AFM order through a phase separation regions [19,22,23].…”
Section: Introductionmentioning
confidence: 99%